High to ultrahigh temperature contact metamorphism and dry partial melting of the Tasiuyak paragneiss, Northern Labrador. (17th April 2014) - Mitchell, R. K.; Indares, A.; Ryan, B.
Abstract Contact aureoles of the anorthositic to granitic plutons of the Mesoproterozoic Nain Plutonic Suite (NPS), Labrador, are particularly well developed in the Palaeoproterozoic granulite facies, metasedimentary, Tasiuyak gneiss. Granulite facies regional metamorphism (MR), c. 1860 Ma, led to biotite dehydration melting of the paragneiss and melt migration, leaving behind biotite‐poor, garnet–sillimanite‐bearing quartzofeldspathic rocks. Subsequently, Tasiuyak gneiss within a c. 1320 Ma contact aureole of the NPS was statically subjected to lower pressure, but higher temperature conditions (MC), leading to a second partial melting event, and the generation of complex mineral assemblages and microstructures, which were controlled to a large extent by the textures of the MR assemblage. This control is clearly seen in scanning electron microscopic images of thin sections and is further supported by phase equilibria modelling. Samples collected within the contact aureole near Anaktalik Brook, west of Nain, Labrador, mainly consist of spinel–cordierite and orthopyroxene–cordierite (or plagioclase) pseudomorphs after MR sillimanite and garnet, respectively, within a quartzofeldspathic matrix. In addition, some samples contain fine‐grained intergrowths of K‐feldspar–quartz–cordierite–orthopyroxene inferred to be pseudomorphs after osumulite. Microstructural evidence of the former melt includes (i) coarse‐grained K‐feldspar–quartz–cordierite–orthopyroxene domains that locally cut the rock fabric and are inferred to represent neosome; (ii) very fine‐ to medium‐grained cordierite–quartz intergrowths interpreted to have formed by a reaction involving dissolution of biotite and feldspar in melt; and (iii) fine‐scale interstitial pools or micro‐cracks filled by feldspar interpreted to have crystallized from melt. Ultrahigh temperature (UHT) conditions during contact metamorphism are supported by (i) solidus temperatures >900 °C estimated for all samples, coupled with extensive textural evidence for contact‐related partial melting; (ii) the inferred (former) presence of osumilite; and (iii) titanium‐in‐quartz thermometry indicating temperatures within error of 900 °C. The UHT environment in which these unusual textures and minerals were developed was likely a consequence of the superposition of more than one contact metamorphic event upon the already relatively anhydrous Tasiuyak gneiss.